Archaic and classical harbours of the Greek world : the Aegean and Eastern Ionian contexts - Mauro, Chiara Maria, (Archaeopress archaeology., 2019)
A study of the archaeology and history of ancient harbours, with particular focus on the Greek world during the Archaic and Classical eras. It questions what locations were the most propitious for the installation of harbours; what kinds of harbour-works were built and for what purpose; and what harbour forms were documented.